Employee Engagement in Media Management: Creativeness and Organizational Development - Georgiades, Stavros (Springer, 2015)
This book explores a major media management topic on the basis of case study research conducted in European, US and Brazilian media companies. More specifically, it examines the dynamics of employee engagement, aiming at organizational development through change. The book contemplates the discipline of Media Management through a management lens and focuses on the concept of employee involvement and its value with regard to successfully introducing change and achieving organizational development. It concentrates on providing the necessary information and organizational arrangements from the points of view of media managers and employees and highlights how this involvement can encourage employees to create and innovate. The book is directed towards researchers and students, as well as practitioners/professionals involved with media organizations.